Dedicated SNAREs and specialized TRIM cargo receptors mediate secretory autophagy. (8th December 2016) - Kimura, Tomonori; Jia, Jingyue; Kumar, Suresh; Choi, Seong Won; Gu, Yuexi; Mudd, Michal; Dupont, Nicolas; Jiang, Shanya; Peters, Ryan; Farzam, Farzin; Jain, Ashish; Lidke, Keith A; et al.
Abstract: Autophagy is a process delivering cytoplasmic components to lysosomes for degradation. Autophagy may, however, play a role in unconventional secretion of leaderless cytosolic proteins. How secretory autophagy diverges from degradative autophagy remains unclear. Here we show that in response to lysosomal damage, the prototypical cytosolic secretory autophagy cargo IL‐1β is recognized by specialized secretory autophagy cargo receptor TRIM16 and that this receptor interacts with the R‐SNARE Sec22b to recruit cargo to the LC3‐II + sequestration membranes. Cargo secretion is unaffected by downregulation of syntaxin 17, a SNARE promoting autophagosome–lysosome fusion and cargo degradation. Instead, Sec22b in combination with plasma membrane syntaxin 3 and syntaxin 4 as well as SNAP‐23 and SNAP‐29 completes cargo secretion. Thus, secretory autophagy utilizes a specialized cytosolic cargo receptor and a dedicated SNARE system. Other unconventionally secreted cargo, such as ferritin, is secreted via the same pathway. Synopsis: Secretory autophagy, an unconventional secretion pathway for cytosolic proteins such as IL‐1β and ferritin, diverges from degradative autophagy by utilization of specialized SNAREs and cargo receptors. Secretory autophagy delivers unconventionally secreted cytosolic cargo including IL‐1β and ferritin in response to lysosomal damage and signaling. TRIM16 acts as a specialized secretory autophagy receptor for IL‐1β. Galectin‐8, TRIM16, and R‐SNARE Sec22b act coordinately in secretory autophagy. Secretory autophagy requires different SNAREs than degradative autophagy. Abstract : Secretory autophagy, an unconventional secretion pathway for cytosolic proteins such as IL‐1β and ferritin, diverges from degradative autophagy by utilization of specialized SNAREs and cargo receptors.